2020
DOI: 10.1519/jsc.0000000000003852
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Curcumin and Fenugreek Soluble Fiber on the Physical Working Capacity at the Fatigue Threshold, Peak Oxygen Consumption, and Time to Exhaustion

Abstract: Curcumin, a polyphenol, has been suggested to improve metabolic byproduct clearance and increase nitric oxide production in working muscle. These purported effects may delay neuromuscular fatigue. Therefore, the purpose of this study was to examine the effects of curcumin in combination with fenugreek (CUR) or fenugreek soluble fiber alone (FEN) on the neuromuscular fatigue threshold (PWCFT), time to exhaustion (Tlim) on a graded exercise test (GXT), and ̇O 2peak in untrained subjects. Forty-seven, college-age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Others have hydrolysed the plasma samples before analysis [ 23 , 25 , 43 ], thus overestimating the true concentration of curcumin in the blood and making it difficult to accurately correlate any observed changes in levels of inflammatory markers to plasma curcumin levels. Finally, although some researchers [ 54 ] have reported that curcumin supplementation increased working capacity at the fatigue threshold and delayed the onset of neuromuscular fatigue, they did not analyse common inflammatory markers such as IL-6, TNF- α , and CK, also hindering comparisons between studies [ 54 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have hydrolysed the plasma samples before analysis [ 23 , 25 , 43 ], thus overestimating the true concentration of curcumin in the blood and making it difficult to accurately correlate any observed changes in levels of inflammatory markers to plasma curcumin levels. Finally, although some researchers [ 54 ] have reported that curcumin supplementation increased working capacity at the fatigue threshold and delayed the onset of neuromuscular fatigue, they did not analyse common inflammatory markers such as IL-6, TNF- α , and CK, also hindering comparisons between studies [ 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…Another study examining the effects of curcumin in combination with fenugreek soluble fibre (CUR + FEN) or fenugreek soluble fibre alone (FEN) on the physical working capacity at the fatigue threshold (PW CFT ), peak oxygen consumption (V̇O 2 peak), and time to exhaustion ( T lim ) on a graded exercise test in untrained subjects for 28 days [ 54 ], showed no effect of curcumin supplementation on V̇O 2 peak or T lim . However, the PW CFT was greater after combined supplementation with curcumin and FEN compared with a placebo in ~20% of subjects [ 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…In another study, 500 mg of HydroCurc (curcumin with LipiSperse) and 500 mg of maltodextrin after exercise reduced capillary lactate dehydrogenase, overall muscle pain, and thigh circumference in young and healthy males with strength training experience . In another randomized controlled trial, curcumin (190 mg/day) and fenugreek fiber (300 mg/day) for 28 days enhanced the neuromuscular fatigue threshold after exercise in untrained college-aged subjects ( n = 47) . A randomized, double-blind, placebo-controlled clinical trial demonstrated that curcumin (1000 mg/day) reduced audio-reaction time, choice-based visual reaction time, and improved memory in 18 volunteers aged 30–65 years .…”
Section: Clinical Trials Of Turmeric and Curcuminmentioning
confidence: 77%
“…180 In another randomized controlled trial, curcumin (190 mg/day) and fenugreek fiber (300 mg/day) for 28 days enhanced the neuromuscular fatigue threshold after exercise in untrained college-aged subjects (n = 47). 181 A randomized, double-blind, placebo-controlled clinical trial demonstrated that curcumin (1000 mg/day) reduced audio-reaction time, choice-based visual reaction time, and improved memory in 18 volunteers aged 30−65 years. 182 This study also showed that curcumin-galactomannan (1000 mg/day) supplementation resulted in a remarkable increase in αand β-waves of the brain and decreased the α/β ratio, audio-reaction time, choicebased visual reaction time, and improved memory in these volunteers.…”
Section: Clinical Trials Of Turmeric and Curcuminmentioning
confidence: 99%
“…Concerning aerobic performance, both significant and non-significant effects were found. So the current data situation about endurance performance is ambiguous [25][26][27][28]. Regarding strength training and the change in body composition, such as fat-free mass and fat mass, no systematic analysis and summaries have yet been conducted.…”
Section: Introductionmentioning
confidence: 99%